NORMA DE DESEMPENHO: SUA IMPLANTAÇÃO JUNTO A PROJETISTAS DA CIDADE DE JOÃO PESSOA - Meira, Alexsandra; Vieira, Sara (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In July 2013, the performance standard (ABNT NBR 15,575) came into force, with the purpose of offering a systemic view of the buildings, focusing on the requirements of the users. In this context, the present work aims to study the effectiveness of the Performance Standard by designers in João Pessoa city. First, a bibliographic review was carried out on the subject, as well as on the structure of the standard, the systems and components that make it up. In addition, from a field research, the work sought to analyze the implementation of the standard with designers, with emphasis on building projects. The results obtained at the end of the research presented a framework of increasing adequacy to the standard of performance in the civil construction of João Pessoa city.